2000
DOI: 10.1021/es981001i
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Pentachlorophenol Using Glow Discharge Plasma Process

Abstract: Pentachlorophenol (PCP), found in wood preservatives and pesticides, is an acutely toxic recalcitrant organochlorine carcinogenic compound. A point-to-plane glow discharge plasma (GDP) process was used to study the destruction of 30-50 ppm (120-188 µM) sodium salt of pentachlorophenol (PCP) in an aqueous solution. PCP was converted to less than 10% of its initial concentration in 1-3 h, at room temperature and low pressure (50 Torr). Effects of varying the headspace gas chemistry, stirring rate, pH, and curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 25 publications
(32 reference statements)
3
56
0
Order By: Relevance
“…To achieve these processes, highly-reactive gas radicals induced by reactions of accelerated electrons with gas molecules are important. Among them, water purification using gas discharge [8][9][10][11][12] is noteworthy because this process utilizes such gas radical species to produce aqueous short-lived species. In this report, we suggest these discharge-induced aqueous species can be used as anti-solvents to promote crystal growth processes.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these processes, highly-reactive gas radicals induced by reactions of accelerated electrons with gas molecules are important. Among them, water purification using gas discharge [8][9][10][11][12] is noteworthy because this process utilizes such gas radical species to produce aqueous short-lived species. In this report, we suggest these discharge-induced aqueous species can be used as anti-solvents to promote crystal growth processes.…”
Section: Introductionmentioning
confidence: 99%
“…Singlet oxygen, generated by corona discharge, oxidized both NADH and NADPH at a much greater rate than controls . Hemoglobin in vitro was not only oxidized, but destroyed by corona discharge , probably by a similar mechanism to that by which corona destroys chlorinated cyclic hydrocarbons [Sharma et al, 2000], organic dyes [Goheen et al, 1992], and carbon tetrachloride [Sharma et al, 1997].…”
Section: Discussionmentioning
confidence: 96%
“…The electron attachment step produces O 2 À , O À , H À , and OH À [Mukkavilli et al, 1988;Kossyi et al, 1992]. We have observed O 3 production near a grounded water source [Goheen et al, 1984;Goheen et al, 1985;Sharma et al, 1997;Sharma et al, 2000], but have identified no specific plausible surface or bulk reaction of ions with ground state molecules contributing to O 3 production. A reaction O 2 À þ H 2 O !…”
Section: Introductionmentioning
confidence: 88%
“…Direct chemical measurements reveal the presence of hydrogen peroxide, hydrogen and oxygen. Electrical discharges in water produced by pulsed high voltage have been known to degrade various chemicals, such as phenols [2,3] polychlorinated biphenyls [4], aniline [5] and monochlorophenols [6,7]. In all of these studies, it has been shown that the species responsible for the degradation of molecules is the hydroxyl radical.…”
Section: Introductionmentioning
confidence: 99%